The effect of intake channel length on water temperature at the intake point of the power plant at Muara Karang power plant - Mardi Wibowo; Hanah Khoirunnisa; Dinar Catur Istiyanto; Aloysius Bagyo Widagdo; Khusnul Setia Wardani (Center of Biomass & Renewable Energy, Diponegoro University, 2024)
Muara Karang Power Plant (MKPP) is one of the main power plants on Java Island in Indonesia. Presently, the Jakarta provincial government has issued a reclamation project on Island G in the marine waters around MKPP. This reclamation effort is predicted to lead to a rise in the seawater temperature around the intake, which MKPP will address with the addition of intake channel of 250 - 957 m. Therefore, this study aimed to determine the effect of intake channel extension on the water temperature at the intake point using numerical modeling comprising hydrodynamics and dispersion advection modules. A total of 10 scenarios were modeled by varying intake channel length and season. The result showed that adding intake channel was less effective because the average water temperature was less than 0.24oC with an effectiveness below 0.78%. Based on the validation of the modeling results on the measurement data, the NRMSD values in west and east seasons were 9.13% and 12.63%, respectively. Under existing conditions, the average and maximum seawater temperatures were 31.40oC and 32.08oC. Meanwhile, by extending intake channel, the average and maximum water temperatures were 31.16oC and 31.60oC. These results showed that by extending intake channel, the temperature at the intake point was generally lower than the existing conditions. Intake channel length was more effective in reducing the temperature at the intake point during west monsoon than east monsoon. Vertically, the temperature at the bottom was relatively colder than near the surface. In west monsoon, the average temperature difference between the bottom and the surface ranged from 0.16-0.21oC, while in east, it was between 0.23 and 0.50oC. In conclusion, the addition of subsequent structures to increase effectiveness was necessary, specifically to hold hot water in east monsoon.